DREAM, a possible answer to the estrogen paradox of the Women's Health Initiative Trial. Issue 1 (January 2022) - Hugh, Judith C.; Haddon, Lacey S.J.; Githaka, John Maringa; Bigras, Gilbert; Hu, Xiuying; Madden, Brittney; Hanson, John; Gabos, Zsolt; Giannakopoulos, Nadia V.; Huang, Fleur; Hitt, Mary M.; McManus, Kirk J.; et al.
Abstract: Estrogen is thought to cause proliferation of all estrogen receptor positive (ER+) breast cancers. Paradoxically, in the Women's Health Initiative Trial, estrogen-only hormone replacement therapy reduced the incidence and mortality of low grade, ER+, HER2- breast cancer. We gave estradiol to 19 post-menopausal women with newly diagnosed low-grade, ER+, HER2- breast cancer in a prospective window of opportunity clinical trial and examined the changes in proliferation and gene expression before and after estradiol treatment. Ki67 decreased in 13/19 (68%) patients and 8/13 (62%) showed a decrease in Risk of Recurrence Score. We chose three prototypical estrogen responders (greatest decrease in ROR) and non-responders (no/minimal change in ROR) and applied a differential gene expression analysis to develop pre-treatment (PRESTO-30 core ) and post-treatment (PRESTO-45 surg ) gene expression profiles. The PRESTO-30 core predicted adjuvant benefit in a published series of tamoxifen, the partial estrogen agonist. Of the 45 genes in the PRESTO-45 surg, thirty contain the Cell cycle genes Homology Region (CHR) motif that binds the class B multi-vulva complex (MuvB) a member of the DREAM (Dimerization partner, retinoblastoma-like proteins, E2F, MuvB) complex responsible for reversible cell cycle arrest or quiescence. There was also near uniform suppression (89%) of the remaining DREAM genes consistent with estrogen induced activation of the DREAM complex to mediate cell cycle block after a short course of estrogens. To our knowledge, this is the first report to show estrogen modulation of DREAM genes and suggest involvement of DREAM pathway associated quiescence in endocrine responsive post-menopausal ER+ breast cancers. Highlights: WHI trial found that estrogen decreases some ER+ post-menopausal breast cancers. Our prospective clinical trial confirmed an anti-proliferative effect of estradiol. DREAM pathway genes were downregulated during the anti-proliferative response. This suggests that estrogen may activate DREAM quiescence of ER+ breast cancers. Abstract : Breast Cancer, Estrogen, DREAM, Hormone therapy.